Beyond Parliamentary Sovereignty and Judicial Supremacy: The Doctrine of Implicit Limits to Constitutional Reform in Latin America - Colon-Rios, Joel (Victoria University of Wellington Law Review, 2013)
This article provides an introduction to the Latin American doctrine of implicit limits to constitutional reform. The article begins by discussing the way in which this doctrine relates to (and differs from) the doctrine of the basic structure, adopted in several common law jurisdictions such as India and Belize. It then examines a decision of the Constitutional Court of Colombia in which the doctrine of implicit limits received one of its clearest formulations. Finally, it is argued that the Latin American approach goes beyond both parliamentary sovereignty and judicial supremacy, providing the constituent people (as opposed to Parliament and the courts) with the final word on the validity of important constitutional changes.